Coupling of formate dehydrogenase to inverse-opal ITO-PSI electrodes for photocatalytic CO2 reduction - Sascha Morlock; Matthias Schenderlein; Kenji Kano; Athina Zouni; Fred Lisdat (Biosensors and Bioelectronics: X, 2023)
Photosynthesis as one of the most fascinating natural processes uses sunlight and CO2 for the preparation of various organic substances. Taking nature as inspiration the present work applies two proteins in an artificial matrix for constructing a biohybrid system allowing light-to-chemical photocataysis. Thus, the protein complexes photosystem I (PSI) and formate dehydrogenase (FDH) are combined with a porous three-dimensional indium tin oxide structure. Direct electron transfer takes place between the electrode material and PSI resulting in cathodic photocurrents. Instead of maximizing the current output, the study focuses on the usage of the excited electrons to drive FDH catalysis. At the enzyme carbon dioxide is reduced to formate with an efficiency of about 15% relative to the number of enhanced photoelectrons. The arrangement is favorable since it enables the conversion of CO2 at rather small applied potential of −0.2 V vs Ag/AgCl and over a longer period of illumination. Conversion efficiency and stability provide a good starting point for further investigations. The reported ITO/PSI/FDH electrode represents a system that combines photocatalysis with enzymatic catalysis allowing the storage of light energy in chemical energy.